Analisis Citra Merek sebagai Variabel Mediasi Antara Persepsi Harga dan Kualitas Produk terhadap Keputusan Pembelian (Studi pada Pengguna Sikat Gigi Pepsodent di Kota Semarang) - Yulia Afinta Sari; Shofif Sobaruddin Akbar; Prianka Ratri Nastiti (Yayasan Literasi Sains Indonesia, 2025)
This study aims to analyze the effect of price perception and product quality on purchase decisions, with brand image as a mediating variable in the context of Pepsodent toothbrush products in Semarang City. The research adopts a quantitative approach using a survey method. A total of 96 respondents were selected through purposive sampling based on specific criteria. Data were collected via an online questionnaire and analyzed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method with the assistance of SmartPLS 4.0 software. The results indicate that price perception has a positive and significant effect on purchase decisions, while product quality does not have a direct effect on purchase decisions. Brand image has a positive and significant effect on purchase decisions and serves as a mediating variable in the relationship between price perception and product quality toward purchase decisions. These findings reinforce the critical role of brand image in shaping consumer decisions, particularly in the context of Fast Moving Consumer Goods (FMCG) products such as toothbrushes, and emphasize the importance of building a strong brand image to enhance purchase decisions, especially amid intense market competition and shifting consumer preferences. This study provides strategic implications for companies in formulating brand value based marketing policies.